Nel gesto, nell’atto. L’arte della performance tra opera e evento (Lebenswelt. Aesthetics and philosophy of experience., 2019)
What kind of art is performance art?  In what sense – if any – can it be defined? This paper is an attempt to answer these questions by drawing on the category of ‘performative gesture’. One crucial manifestation of the character of performance art is the way it challenges our traditional ideas about what art is. A pivotal point is that performance art does not hold up to the traditional notion of artistic creativity as either a process of ‘production’ or ‘reproduction’. It is rather committed to putting the focus of artistic creativity on a special kind of gestures, differing from both the gestures of traditional art and from the gestures of theater. Performative gestures do not ‘bring anything into being’; analogously, they do not ‘mimic’ nor ‘represent’. Instead, they suggest the worrying idea that everything and anything can be considered art: not only every object, but even every ordinary act in everyday life. In this sense, performance art attempts at blurring the boundaries between art and life.